The Development Teaching Materials of Learning Technology based on Character Building (Research, Society and Development, 2019)
This study aimed to produce teaching materials about learning technology whose contents are integrated about the strengthening of characters packed using“We Can Do It”or "KITA BISA" formula. The word "KITA" represents lecturers and students, while "BISA" is an acronym of the characters Bernalar (Intelligent), Integritas (Integrity), Santun (Polite), and Adil (Fair). The developed teaching material was intended for students, lecturers, and observers of education, especially in the field of learning technology. The data were collected through literature study on several references that were in accordance with the research problem. This research resulted: 1) model of students’ character reinforcement evaluation, and 2)systematic teaching learning technology materials consist of 9 chapters: (1) the development, the area and the foundation of the philosophy learning technology, (2) the theoretical foundation of learning technology and elements of educational technology, (3) creation and management, (4) use and utilization, (5) process and learning resources, (6) ) facilitating learning, (7) performance improvement, (8) professional ethics and educational technology, and (9) online learning.